IDENTIFIKASI POTENSI DAYA TARIK EKOWISATA DI ZONA PEMANFAATAN TAMAN NASIONAL MANUSELA KECAMATAN SERAM UTARA KABUPATEN MALUKU TENGAH - Andjela Sahupala (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
The aim of the study was to determine the potential of flora and fauna in the Masihulan TNM Resort Utilization Zone. The methods used in this research are observation, rapid assessment, interviews. Data analysis was carried out through descriptive analysis. The results showed that 35 species of flora found along the route consisted of 18 families, Moraceae being the dominating family for flora species. For potential fauna 35 species 14 families. The Psitisidae family (11 species) predominates. The existing potential for flora and fauna species needs to be complemented by facilities in the form of interpretation lines and the readiness of local guides who can assist tourists when carrying out interpretation activities on the observation path of the Masihulan Resort utilization zone. The Masihulan Village community also supports the management of the Utilization Zone if needed by the TNM Office. Forms of activities that support and are carried out by the Masihulan Community in the form of becoming local guides, porters, homestay providers, food and drink, and means of transportation while in the area.